Validating and implementing the informal learning behavior scale - Willis, Colin Michael Groden, author; Kraiger, Kurt, advisor; Fisher, Gwen, committee member; Cleary, Anne, committee member; Maynard, Travis, committee member (Colorado State University. Libraries, 2019)
The present study developed and tested a measure of informal learning behaviors for the workplace. Informal learning refers to any learning that occurs outside of formal and structured instructional settings. The literature has recently called for validated and reliable measures of informal learning, following a growing body of evidence that informal learning is both extremely prevalent in the workplace and important to high performance at work. Two connected studies were conducted to address this gap in the literature. In the first, a thorough literature review was conducted to identify a subset of informal learning that was intentional and observable at work. Six dimensions of informal learning were proposed to meet these criteria: planning, socializing, reflecting, experimenting, adapting, and scanning. Items were written and reviewed by subject matter experts. Participants were recruited from a research pool and an online MTurk pool to respond to the initial set of items and several additional scales used for convergent and discriminant validation. Analyses found strong support for a 23-item, five-factor model combining the planning and scanning dimensions and strong relationships between the dimensions and metacognition, motivation to learn, learning goal orientation, and a prior informal learning scale. Conversely, there were weak or negative relationships between the dimensions and prove performance goal orientation, as hypothesized. The second study was conducted to confirm the 23 item, five-factor model of the scale in a new, organizational sample and collect additional validity evidence by testing a model linking informal learning to self-regulation, support for learning, and job performance. Participants completed measures of the informal learning behavior scale, sleep quantity and quality, occupational self-efficacy, and support for learning in the organization. Responses were then matched to archival performance data. Analyses confirmed the hypothesized structure of the scale but found only some support for the proposed model. Sleep had no impact on either occupational self-efficacy or informal learning behaviors. Perceived support for learning was not related to informal learning behaviors. Occupational self-efficacy was related to informal learning, and the experimenting dimension predicted both job performance and job potential. The resulting scale is a reliable measure of five informal learning behavioral dimensions with a developing body of validity evidence supporting its use.
Keywords: experimenting; reflecting; training; informal learning; assessment; scale development